2015
DOI: 10.1155/2015/764641
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis Related Inflammatory Mediators: Role of the IL‐10 Cytokine Family

Abstract: Importance of chronic fibroproliferative diseases (FDs) including pulmonary fibrosis, chronic kidney diseases, inflammatory bowel disease, and cardiovascular or liver fibrosis is rapidly increasing and they have become a major public health problem. According to some estimates about 45% of all deaths are attributed to FDs in the developed world. Independently of their etiology the common hallmark of FDs is chronic inflammation. Infiltrating immune cells, endothelial, epithelial, and other resident cells of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
200
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(209 citation statements)
references
References 165 publications
(181 reference statements)
3
200
0
6
Order By: Relevance
“…The possible role of IL-10 family members such as IL-20, IL-22 and, more recently, IL-24/mda-7, started to be delineated more in fibrosis development (13). Even though the general player molecules involved in HSC cell activation and transition into myofibroblasts have been studied deeply, the possible role of IL-24/mda7 needs to be investigated in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The possible role of IL-10 family members such as IL-20, IL-22 and, more recently, IL-24/mda-7, started to be delineated more in fibrosis development (13). Even though the general player molecules involved in HSC cell activation and transition into myofibroblasts have been studied deeply, the possible role of IL-24/mda7 needs to be investigated in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although, expression level of IL-20 and IL-22 were evaluated in human and mice stellate cells, comparing IL-24/mda-7 expression in normal or activated HSCs is rare (13,26). New research revealed that IL-22, another member of the IL-10 cytokine family, promotes HSC proliferation and activation, prevents HSC apoptosis, induces the overexpression of HSC growth factors and fibrosis markers including Col-IV, laminin and hyaluronic acid (27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations